Reliability assessment of the malay version visual comfort questionnaire for schoolchildren with visual impairment - Pui Theng Yong; Zainora Mohammed; Norliza Mohamad Fadzil; Mohd Harimi Abd Rahman; Mohd Izzuddin Hairol; Sumithira Narayanasamy (PLoS ONE, 2025)
Lighting adjustments are crucial in vision rehabilitation to enhance visual function and promote visual comfort. However, there is a lack of validated questionnaires to assess lighting needs among schoolchildren with visual impairment. Given the limited knowledge of their specific need for reading and learning activities, a translated and reliable instrument is essential for guiding evidence-based support. This study aims to translate, adapt, and assess face validity, content validity and reliability of the Malay version Visual Comfort Questionnaire (VCQ-M). This is a cross-sectional study that was carried out from November 2022 to January 2023. Forward-backwards translation was used to translate the items in the questionnaire from English into Malay. Face and content validity of the translated questionnaire were determined to ensure comprehensibility and cultural adaptability. Ten normal-sighted adults participated in face validation. Five optometrists were recruited as expert panels to rate the questionnaire items. The inter-rater reliability of the questionnaire was assessed using Fleiss’ Kappa and the inter-class correlation coefficient (ICC). To determine the internal consistency of VCQ-M, 42 subjects with visual impairment from a special secondary school were recruited in this study to complete the VCQ-M after reading a paragraph comprised of 50 words under lighting of 125 lux. Internal consistency of VCQ-M was analysed using Cronbach’s alpha with composite reliability for confirmation. The face validity showed 91.0% of overall agreement, while the content validity index for the item was above 0.80 at item-level and scale-level. The translated VCQ-M has acceptable Fleiss’ Kappa inter-rater reliability for relevance (κ = 0.54) and comprehensibility (κ = 0.44), as well as ICC inter-rater reliability for relevance (ICC(3, 5) = 0.88) and comprehensibility (ICC(3, 5) = 0.73). The Cronbach’s alpha (α = 0.92) showed acceptable internal consistency and confirmed with Dijkstra-Henseler’s rho (ρA = 0.95) and Jöreskog’s rho (ρc = 0.94). The VCQ-M shows an acceptable face validity index, content validity index, inter-rater reliability and internal consistency. This study represents a first-stage validation focused on internal consistency. Construct validity was not assessed, and thus the psychometric evaluation is partial and preliminary. However, the findings support using VCQ-M as a reliable and valid questionnaire to assess visual comfort among Malay-speaking schoolchildren with visual impairment.